Corrosion-resistant and fire-resistant coating containing silicon dioxide aerogel for steel structure

By using anti-corrosion and fire-resistant coatings containing nano-silicon dioxide aerogel and additives on the steel structure, the corrosion and fire resistance problems of the steel structure in humid environments and fire conditions are solved, and significant anti-corrosion, fire resistance and anti-bacteriality are achieved. Performance improvement.

CN119463596AInactive Publication Date: 2025-02-18UNIV OF SCI & TECH OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411436732.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Steel structures are prone to corrosion and insufficient fire resistance in humid environments and fire conditions, resulting in reduced service life and increased building safety risks.

Method used

Anticorrosion and fire-resistant coatings containing nanosilicon dioxide aerogels, additives and inorganic fillers are used to form hybrid crosslinks through the synergistic effect of the isothiazolinone structure in the additive and the halogen-free flame retardant elements nitrogen, phosphorus and silicon. The network structure improves the anticorrosion, fire resistance, antibacterial and anti-aging properties of the paint.

Benefits of technology

It significantly improves the corrosion and fire resistance of steel structures, extends the service life, enhances the fire resistance, and can effectively protect the safety of buildings in the event of fire.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 4NWLDCCJSYROSCCURHA1KLTJA9WCMSMDNWBYI5CY
    Figure 4NWLDCCJSYROSCCURHA1KLTJA9WCMSMDNWBYI5CY
  • Figure 69OJIWE42EKIU0LJED5X0V3ARJMIJLRKSYY3JQU0
    Figure 69OJIWE42EKIU0LJED5X0V3ARJMIJLRKSYY3JQU0
  • Figure 9KGBUPUJFGKTLWEIPFC1A6H81OFSDQSYRC00G4BY
    Figure 9KGBUPUJFGKTLWEIPFC1A6H81OFSDQSYRC00G4BY
Patent Text Reader

Abstract

The invention discloses an anticorrosive and fireproof coating containing silicon dioxide aerogel for a steel structure, and belongs to the technical field of coatings. The anticorrosive and fireproof coating is prepared from the following raw materials in parts by weight: 35 to 45 parts of acrylic emulsion, 10 to 20 parts of nano silicon dioxide aerogel, 12 to 17 parts of auxiliaries, 45 to 60 parts of inorganic filler, 0.2 to 0.8 part of wetting agent and 0.05 to 0.2 part of flatting agent. The auxiliary agent contains an isothiazolinone structure and rich halogen-free flame-retardant elements such as nitrogen, phosphorus and silicon, inorganic fillers such as titanium dioxide and sepiolite powder are added, the nano silicon dioxide aerogel and the auxiliary agent interact, and the auxiliary agent and the acrylic emulsion interact, so that a hybrid cross-linked network structure is formed among various raw materials, and the flame-retardant performance of the coating is improved. Due to the network structure, the coating has more efficient and lasting properties such as corrosion resistance, fire resistance, antibacterial property, aging resistance and wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings, and in particular relates to an anticorrosion and fire retardant coating containing silica aerogel for steel structures. Background Art

[0002] As a form of high-rise building structure, steel structure is widely used in the construction industry due to its high strength, light weight, good elongation, earthquake resistance and short construction period. It shows strong vitality in super high-rise and large-span buildings.

[0003] However, humidity, rain and other environments and the presence of harmful microorganisms can cause bacteria to grow in steel structure coatings, which in turn affects their use and even reduces their service life.

[0004] In addition, the fire resistance of steel structure buildings is worse than that of masonry and reinforced concrete structures. The most fatal weakness of steel structure is that the fire resistance of steel is very poor. The internal crystal structure of steel is very sensitive to temperature. The mechanical strength of steel decreases with the increase of temperature. At about 500℃, its strength drops to 40% to 50%. The mechanical properties of steel, such as yield point, compressive strength, elastic modulus and load capacity, all drop rapidly, and soon lose their supporting capacity, causing the building to collapse. Although steel is a non-combustible material, it is a good conductor of heat. Once it encounters a high-temperature flame, its supporting force will be destroyed within a certain period of time. The fire resistance limit of commonly used steel structure components is only 15 to 30 minutes. This shows that the fire resistance limit of steel components not covered with a fire-resistant protective layer is far from the requirements of fire protection regulations and cannot meet the requirements for building fire protection in the event of a fire. Summary of the invention

[0005] The purpose of the present invention is to overcome the defects of the prior art and provide an anticorrosion and fire retardant coating containing silica aerogel for steel structures.

[0006] The purpose of the present invention can be achieved by the following technical solutions: A corrosion resistant and fireproof coating containing silica aerogel for steel structure comprises the following raw materials in parts by weight: 35-45 parts of acrylic emulsion, 10-20 parts of nano silica aerogel, 12-17 parts of auxiliary agent, 45-60 parts of inorganic filler, 0.2-0.8 parts of wetting agent and 0.05-0.2 parts of leveling agent.

[0007] Nano-silica aerogel is a material with excellent properties. Adding it to paint can give the paint properties such as lightness, heat insulation, and insulation.

[0008] Furthermore, the auxiliary agent is prepared by the following steps: S1. Blow nitrogen gas into a dry three-necked flask for 30 minutes to remove the air in the flask, then add tri(2-chloroethyl) phosphate, anhydrous sodium carbonate and deionized water into the flask, mix and stir evenly, then slowly add meglumine, stir and heat to 80°C, react at 80°C for 3 hours, cool to room temperature after the reaction, distill under reduced pressure, purify by column chromatography (the eluent is a mixed solvent of benzene and methanol, the volume ratio of benzene and methanol is 9:1), finally distill under reduced pressure to remove the eluent to obtain intermediate 1; the amount ratio of tri(2-chloroethyl) phosphate, meglumine, anhydrous sodium carbonate and deionized water is 14.4mL:28.4g:14.8g:180mL; Anhydrous sodium carbonate is used as an acid-binding agent, and the molar ratio of tri(2-chloroethyl) phosphate to meglumine is controlled to be 1:2.05-2.1, then -Cl of tri(2-chloroethyl) phosphate and -NH- of meglumine undergo nucleophilic substitution reaction, and the reaction process is as follows: S2, replace the air in the dry three-necked flask with nitrogen, then add melamine and DMSO (dimethyl sulfoxide), and then slowly add 3-isocyanate propyltrimethoxysilane, stir and react at room temperature for 1 hour, distill under reduced pressure, purify by column chromatography (the eluent is a mixed solvent of cyclohexane and ethyl acetate, and the volume ratio of cyclohexane and ethyl acetate is 1:1), and finally distill under reduced pressure to remove the eluent. The whole process is carried out under nitrogen protection to obtain intermediate 2; the amount ratio of melamine, 3-isocyanate propyltrimethoxysilane and DMSO is 10.8g:15.1mL:100mL; The molar ratio of melamine to 3-isocyanate propyl trimethoxy silane is controlled to be 1.05-1.1:1, and melamine and 3-isocyanate propyl trimethoxy silane undergo an addition reaction at room temperature. The reaction equation is as follows: S3, nitrogen was blown into a dry three-necked flask for 30 minutes to remove the air in the flask, and then intermediate 2, triethylamine and DMF (N,N-dimethylformamide) were added, and stirred until completely dissolved, and then isothiazolinone was slowly added. After the addition was completed, the temperature was controlled at 0°C, and the reaction was carried out at 0°C for 4 hours. After the reaction was completed, it was distilled under reduced pressure, purified by column chromatography (the eluent was a mixed solvent of chloroform and ether, and the volume ratio of chloroform and ether was 8:2), and distilled under reduced pressure to obtain intermediate 3; the amount ratio of intermediate 2, isothiazolinone, triethylamine and DMSO was 25.1g:8.4mL:11.7mL:130mL; Triethylamine was used as an acid binding agent to control the molar ratio of intermediate 2 to isothiazolinone to be 1.05-1.1:1. 2 It undergoes a nucleophilic substitution reaction with the -Cl of isothiazolinone. The reaction process is as follows: S4. Blow nitrogen gas into a dry three-necked flask for 30 minutes to remove the air in the flask, then add intermediate 1, pyridine and DMF, stir until completely dissolved, then slowly add intermediate 3, after the addition is complete, react at room temperature for 8 hours, and after the reaction is completed, distill under reduced pressure, purify by column chromatography (a mixed solvent of benzene and ethyl acetate is selected as the eluent, and the volume ratio of benzene and ethyl acetate is 8:2), and distill under reduced pressure to obtain an auxiliary agent; the amount ratio of intermediate 1, intermediate 3, pyridine and DMF is 26g:17.8g:4.2mL:200mL.

[0009] Pyridine is used as an acid binding agent to control the molar ratio of intermediate 1 to intermediate 3 to be 1.05-1.1:1. The -Cl of intermediate 1 and the -NH 2 A nucleophilic substitution reaction occurs, and the reaction process is as follows: The additive contains halogen-free flame retardant elements nitrogen, phosphorus and silicon. The synergistic effect of the three makes the coating have an efficient and safe fireproof effect. The phosphorus element in the additive provides an acid source to promote the formation of carbonized products; the nitrogen element provides a gas source, which can make the system expand and foam, and also promotes the formation of the carbonized layer to form porous foam carbon; the silicon element generates an inorganic heat-insulating protective layer containing -Si-O bonds and -Si-C- bonds during combustion, which not only prevents the decomposition products generated by combustion from escaping, but also inhibits the thermal decomposition of the coating, achieving the purpose of high flame retardancy, low smoke emission and low harmfulness.

[0010] The additive contains isothiazolinone structure, which can break the bonds of bacteria and algae proteins, thereby killing bacteria and algae. After the isothiazolinone structure comes into contact with microorganisms, it can quickly and irreversibly inhibit their growth, thereby causing the death of microbial cells. At the same time, the isothiazolinone structure has high bactericidal efficiency, good degradability, good compatibility, and low cost of use. Therefore, adding additives containing isothiazolinone structure into the coating can improve the antibacterial properties of the coating and extend its service life.

[0011] One end of the additive contains silaneoxy groups, which can hydrolyze and condense to form covalent bonds with abundant hydroxyl groups on the surfaces of nano-silica aerogel and inorganic filler to form crosslinks, thereby making the nano-silica aerogel and inorganic filler highly dispersed in the coating, giving full play to the effects of heat insulation, anti-aging, anti-corrosion, anti-friction and the like; the other end of the additive contains abundant hydroxyl groups, which can form hydrogen bonds with carboxyl groups in acrylic emulsion, so that the additive can also be uniformly dispersed and stably present in the coating; therefore, the interaction between the inorganic filler, the nano-silica aerogel and the additive, and the interaction between the additive and the acrylic emulsion form a hybrid crosslinked network structure between the several raw materials, and the network structure makes the corrosion resistance, fire resistance, antibacterial property, aging resistance and wear resistance of the coating of the invention more efficient and durable.

[0012] Furthermore, the inorganic filler is prepared by compounding titanium dioxide, sepiolite powder, expandable graphite and talcum powder in a mass ratio of 2:1:1:1.

[0013] Titanium dioxide can absorb or reflect ultraviolet rays, protecting the paint from damage by ultraviolet rays, thereby extending the service life of the paint. At the same time, titanium dioxide can also improve the paint's antibacterial properties, hiding power, tinting power and scrub resistance. Sepiolite has good corrosion resistance, radiation resistance, thermal insulation, friction resistance, and anti-penetration properties. The large amount of lightweight, non-combustible carbon layer formed by expandable graphite in a fire can effectively block the radiation of heat to the substrate and effectively protect the substrate. At the same time, graphite is a good conductor of electricity. Adding it to the paint can prevent the accumulation of static charges and achieve the dual effects of fire prevention and anti-static electricity. Adding talcum powder to the paint can reduce manufacturing costs, increase the hardness of the paint film, increase the fineness of the paint, improve the shape stability of the product, increase the tensile strength, shear strength, and pressure strength, and improve the rheology and leveling of the paint, and improve the weather resistance of the paint. Furthermore, the wetting agent is one or more of dioctyl sodium sulfosuccinate, HY-1600 wetting agent, HY-1608 wetting agent, and HY-1608A wetting agent.

[0014] Furthermore, the leveling agent is one or more of BYK-333 leveling agent, BYK-306 leveling agent, and BYK-248 leveling agent.

[0015] The beneficial effects of the present invention are as follows: the additive contains an isothiazolinone structure and rich halogen-free flame retardant elements such as nitrogen, phosphorus and silicon, and there is interaction between inorganic fillers such as titanium dioxide and sepiolite powder, nano-silicon dioxide aerogel and the additive, and there is interaction between the additive and acrylic emulsion. Therefore, a hybrid cross-linked network structure is formed between the various raw materials, and the network structure enables the coating of the present invention to have more efficient and lasting anti-corrosion, fire resistance, antibacterial, anti-aging and wear resistance and other properties. DETAILED DESCRIPTION

[0016] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0017] Preparation of auxiliary agent, the specific steps are as follows: S1. Blow nitrogen gas into a 500 mL dry three-necked flask for 30 min to remove the air in the flask, then add 14.4 mL of tris(2-chloroethyl)phosphate, 14.8 g of anhydrous sodium carbonate and 180 mL of deionized water into the flask, mix and stir evenly, then slowly add 28.4 g of meglumine, stir and heat to 80°C, react at 80°C for 3 h, cool to room temperature after the reaction, distill under reduced pressure, purify by column chromatography (the eluent is a mixed solvent of benzene and methanol, the volume ratio of benzene and methanol is 9:1), finally distill under reduced pressure to remove the eluent to obtain intermediate 1; S2, replace the air in a 250mL dry three-necked flask with nitrogen, then add 10.8g of melamine and 100mL of DMSO, and then slowly add 15.1mL of 3-isocyanatepropyltrimethoxysilane, stir and react at room temperature for 1h, distill under reduced pressure, purify by column chromatography (the eluent is a mixed solvent of cyclohexane and ethyl acetate, and the volume ratio of cyclohexane and ethyl acetate is 1:1), and finally remove the eluent by distillation under reduced pressure. The whole process is carried out under nitrogen protection to obtain intermediate 2; S3, nitrogen was blown into a 250 mL dry three-necked flask for 30 min to remove the air in the flask, and then 25.1 g of intermediate 2, 11.7 mL of triethylamine and 130 mL of DMF were added, and stirred until completely dissolved, and then 8.4 mL of isothiazolinone was slowly added. After the addition was completed, the temperature was controlled at 0°C, and the reaction was carried out at 0°C for 4 h. After the reaction was completed, it was distilled under reduced pressure, purified by column chromatography (the eluent was a mixed solvent of chloroform and diethyl ether, and the volume ratio of chloroform and diethyl ether was 8:2), and distilled under reduced pressure to obtain intermediate 3; S4. Blow nitrogen gas into a 500 mL dry three-necked flask for 30 min to remove the air in the flask, then add 26 g of intermediate 1, 4.2 mL of pyridine and 200 mL of DMF, stir until completely dissolved, then slowly add 17.8 g of intermediate 3, after the addition is complete, react at room temperature for 8 h, and after the reaction is completed, distill under reduced pressure, purify by column chromatography (a mixed solvent of benzene and ethyl acetate is selected as the eluent, and the volume ratio of benzene and ethyl acetate is 8:2), and distill under reduced pressure to obtain an auxiliary agent.

[0018] Preparation of anti-corrosion and fire-retardant coating, the specific steps are as follows: 35 parts of acrylic emulsion, 10 parts of nano-silica aerogel, 12 parts of the additive prepared in Example 1, 18 parts of titanium dioxide, 9 parts of sepiolite powder, 9 parts of expandable graphite, 9 parts of talc, 0.2 parts of dioctyl sodium sulfosuccinate, and 0.05 parts of BYK-333 leveling agent were weighed in parts by weight and added in sequence to a high-speed disperser for mixing and dispersion, allowed to stand for aging for 10 hours, and packaged to obtain an anti-corrosion and fire-retardant coating.

[0019] Preparation of anti-corrosion and fire-retardant coating, the specific steps are as follows: Weigh 40 parts of acrylic emulsion, 18 parts of nano-silica aerogel, 15 parts of the additive prepared in Example 1, 20 parts of titanium dioxide, 10 parts of sepiolite powder, 10 parts of expandable graphite, 10 parts of talcum powder, 0.6 parts of HY-1600 wetting agent, and 0.1 parts of BYK-306 leveling agent in parts by weight, add them in a high-speed disperser in sequence for mixing and dispersion, let stand for aging for 12 hours, and meter and package to obtain an anti-corrosion and fire-retardant coating.

[0020] Preparation of anti-corrosion and fire-retardant coating, the specific steps are as follows: Weigh 45 parts of acrylic emulsion, 20 parts of nano-silica aerogel, 17 parts of the additive prepared in Example 1, 24 parts of titanium dioxide, 12 parts of sepiolite powder, 12 parts of expandable graphite, 12 parts of talcum powder, 0.8 parts of HY-1608A wetting agent, and 0.2 parts of BYK-248 leveling agent in parts by weight, and add them in a high-speed disperser in sequence for mixing and dispersion, stand and age for 15 hours, and measure and package to obtain an anti-corrosion and fire-retardant coating.

[0021] Comparative Example 1 The specific steps for preparing the coating are as follows: The remaining steps remain unchanged, and the additives in Example 4 are removed to prepare the coating.

[0022] Comparative Example 2 The specific steps for preparing the coating are as follows: The remaining steps remain unchanged, and the additives in Example 4 are replaced by 8 parts of melamine, 8 parts of ammonium polyphosphate, and 1 part of isothiazolinone to prepare a coating.

[0023] Performance Testing The coatings of Examples 2-4 and Comparative Examples 1-2 were subjected to the following performance tests according to GB14907-2018 "Fire Retardant Coatings for Steel Structures", and the test results are shown in Table 1 below: Table 1 Antibacterial properties were tested in accordance with GB / T21866-2008 "Determination of antibacterial properties and antibacterial effects of antibacterial coatings (paint films)". The test results are shown in Table 2 below: Table 2 “-” means no antibacterial property.

[0024] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0025] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. An anticorrosion and fire retardant coating containing silica aerogel for steel structure, characterized in that: The invention comprises the following raw materials in parts by weight: 35-45 parts of acrylic emulsion, 10-20 parts of nano-silica aerogel, 12-17 parts of auxiliary agent, 45-60 parts of inorganic filler, 0.2-0.8 parts of wetting agent and 0.05-0.2 parts of leveling agent; Wherein, the auxiliary agent is prepared by the following steps: S1. After nitrogen is blown into the flask, tri(2-chloroethyl)phosphate, anhydrous sodium carbonate and deionized water are added into the flask, mixed, and meglumine is added. The mixture is reacted at 80° C. for 3 h, cooled, and distilled under reduced pressure. The mixture is purified by column chromatography and distilled under reduced pressure to obtain intermediate 1. S2, after replacing the air in the flask with nitrogen, add melamine, DMSO, and then add 3-isocyanatepropyltrimethoxysilane, react at room temperature for 1 hour, distill under reduced pressure, purify by column chromatography, and distill under reduced pressure to obtain intermediate 2; S3, nitrogen purged the flask, added intermediate 2, triethylamine and DMF, stirred, added isothiazolinone, reacted at 0°C for 4h, distilled under reduced pressure, purified by column chromatography, and distilled under reduced pressure to obtain intermediate 3; S4. Purge the flask with nitrogen, add intermediate 1, pyridine and DMF, stir, add intermediate 3, react at room temperature for 8 hours, distill under reduced pressure, purify by column chromatography, and distill under reduced pressure to obtain an auxiliary agent.

2. The anticorrosion and fire retardant coating containing silica aerogel for steel structure according to claim 1, characterized in that: The usage ratio of tri(2-chloroethyl)phosphate, meglumine, anhydrous sodium carbonate and deionized water in step S1 is 14.4 mL:28.4 g:14.8 g:180 mL.

3. The anticorrosion and fire retardant coating containing silica aerogel for steel structure according to claim 1, characterized in that: The usage ratio of melamine, 3-isocyanatepropyltrimethoxysilane and DMSO in step S2 is 10.8 g:15.1 mL:100 mL.

4. The anticorrosion and fire retardant coating containing silica aerogel for steel structure according to claim 1, characterized in that: The usage ratio of intermediate 2, isothiazolinone, triethylamine and DMSO in step S3 is 25.1 g:8.4 mL:11.7 mL:130 mL.

5. The anticorrosion and fire retardant coating containing silica aerogel for steel structure according to claim 1, characterized in that: The usage ratio of intermediate 1, intermediate 3, pyridine and DMF in step S4 is 26 g:17.8 g:4.2 mL:200 mL.

6. The anticorrosion and fire retardant coating containing silica aerogel for steel structure according to claim 1, characterized in that: The inorganic filler is prepared by mixing titanium dioxide, sepiolite powder, expandable graphite and talcum powder in a mass ratio of 2:1:1:

1.

7. The anticorrosion and fire retardant coating containing silica aerogel for steel structure according to claim 1, characterized in that: The wetting agent is one or more of dioctyl sodium sulfosuccinate, HY-1600 wetting agent, HY-1608 wetting agent, and HY-1608A wetting agent.

8. The anticorrosion and fire retardant coating containing silica aerogel for steel structure according to claim 1, characterized in that: The leveling agent is one or more of BYK-333 leveling agent, BYK-306 leveling agent, and BYK-248 leveling agent.